Retensi Karyawan Gen Y dan Z: Pentingnya Manajemen Talenta dan Kepuasan Kerja - Yani, Ni Wayan Merry Nirmala; Saputra, I Gusti Ngurah Widya Hadi (Jurnal Ilmu Manajemen, 2023)
Management of human resources in the present era is undoubtedly a concern for organizations to be able to maintain their sustainability. The current dominance of millennial generation workers (Generation Y and Z) must be managed properly by the organization so that it can achieve its goals to the fullest. This research then tries to explore the relationship between talent management and job satisfaction on employee retention among Y and Z generation employees in Denpasar City. Furthermore, exploration is carried out by looking at the mediating effect of job satisfaction on the relationship between talent management and employee retention. Sample data from 100 Y and Z generation workers in Denpasar City were then processed using SEM-PLS. The results then show that there is a significant positive correlation between job satisfaction and talent management on Y and Z generation employee retention in Denpasar City. The mediating role is also shown by the job satisfaction variable in the relationship between talent management and employee retention. This shows the importance of an effective talent management strategy for organizations in fulfilling employee job satisfaction so that it can assist in employee retention efforts.